PENCAPAIAN KOMPETENSI LABORATORIUM SUCTIONING MELALUI PEER LEARNING DAN VIDEO DENGAN PENDEKATAN MODEL ARCS - NIKMATUL FADILAH, - (2014)
Public demand on professional nursing care spur nurse to achieve competency by innovative and effective learning. The objective of this study is to analyze achievement of suctioning competence through peer leaming and video. This study used a posttest only control group design. The sample was student of Prodi D m Keperawatan Kampus Sutopo Surabaya who met criteria listed active student, graduating prerequisite courses ofKDM II and presence of lectures at least 90%. The sample was recruited using systematic random sampling, each group 10 students. Independent variable is peer learning and video, and dependent variables are peer learning experience, learning motivation and competence of suctioning. Data analysis is using the mann whitney. The results showed: 1) peer learning and video increased interaction and collaboration; increase self-confidence; decrease anxiety; freedom of communication; and more support. Respondent still put the laboratory instructor as the main learning resource. Peer learning is embedded interest an educator. They are interested on peer learning soon, 2) both individual self-learning with the SOP skills and peer learning ~ith video were able to build on very high levels motivation and reach competent and proficient. Students who are adolescents amplify the benefits, but knowledge is minimal distance between the tutor-tutee; lacking management can reduce the achievement of objectives. The difference of learning behavior model, specifically on the context learning is impediment. These are recommended for instructor: 1) identify learning behavior model, 2) prepare a tutor on knowledge, management and leadership, 3) preparation is gradually learning both in time and SUbjects.